2015
DOI: 10.1016/j.clml.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Azacitidine in De Novo and Relapsed Acute Myeloid Leukemia: A Retrospective Comparative Study

Abstract: Introduction: Azacitidine is a therapeutic alternative to low-dose cytarabine in patients with acute myeloid leukemia (AML) who are unfit for intensive chemotherapy. Patients and Methods: We retrospectively analyzed all AML patients treated with azacitidine at the University Hospital Zurich and the Kantonsspital Munsterlingen between January 2005 and December 2011. The primary end point was overall survival (OS). Results: Thirty-eight patients were included in the analysis. Twenty-one (55%) patients had newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…To our knowledge, this international study represents the largest reported experience of HMA use in patients with RR-AML. [8][9][10][16][17][18] As expected, patients in this cohort were older (median age 65 years) and exhibited high-risk disease features, such as poor-risk karyotypes (40%) and secondary AML (30%). Although the OS for the entire cohort was poor (median, 6.7 months), a significant subset of patients (16%) achieved CR/CRi with HMAs and achieved a median OS of 21.2 months (95% CI, 16.3-28.6).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To our knowledge, this international study represents the largest reported experience of HMA use in patients with RR-AML. [8][9][10][16][17][18] As expected, patients in this cohort were older (median age 65 years) and exhibited high-risk disease features, such as poor-risk karyotypes (40%) and secondary AML (30%). Although the OS for the entire cohort was poor (median, 6.7 months), a significant subset of patients (16%) achieved CR/CRi with HMAs and achieved a median OS of 21.2 months (95% CI, 16.3-28.6).…”
Section: Discussionmentioning
confidence: 84%
“…1,2,7 The role of HMAs in patients with RR-AML after failure of IC is not well studied, with data limited to small and/or single-institution retrospective studies. [8][9][10] The objective of this international retrospective study was to examine the patterns of use and efficacy of HMAs in a multicenter cohort of RR-AML patients and to assess for clinical and laboratory markers that could identify patients most likely to benefit from HMAs.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of our historical control group is in line with published data. [2][3][4][5] For instance, the French DATAML registry reported 97 similar patients who achieved a 19% CR rate and a median OS of 9.6 months. 5 VEN-AZA salvage therapy has been reported in several publications.…”
Section: Discussionmentioning
confidence: 99%
“…The response rates in this population of patients are 15%-20% and the overall survival (OS) is approximately 7 months. [2][3][4][5] Therefore, new therapeutic strategies are needed. Venetoclax (VEN), an inhibitor of the antiapoptotic protein BCL-2, shows antileukemic activity by restoring intrinsic apoptosis in AML blasts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found six other retrospective studies that used hypomethylating agents in patients with relapsed/refractory AML. In 2015, Gemueden et al (n = 14) reported a MOS of 11 months in patients who received AZA [ 15 ]. Itzykson et al studied the outcomes of patients with relapsed (n = 67) and refractory (n = 63) AML who received AZA [ 16 ].…”
Section: Discussionmentioning
confidence: 99%